2018
DOI: 10.1002/2017jd027629
|View full text |Cite
|
Sign up to set email alerts
|

A Case Study of Low‐Level Jets in Yerevan Simulated by the WRF Model

Abstract: Capabilities of high‐resolution (3 km) Weather Research and Forecasting (WRF) simulations to reproduce topographically induced mountain‐valley winds and low‐level jets (LLJs) in Yerevan have been evaluated using high‐frequency observational and modeled data. High sensitivities of simulations of near‐surface winds and LLJ characteristics observed on 4 July 2015 to both boundary layer and initial and lateral boundary conditions setup have been demonstrated. Among the nine tested planetary boundary layer (PBL) pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 53 publications
1
10
0
2
Order By: Relevance
“…The latter leads to more accurate modeling of low‐level orographically induced flows, convergence centers, and moisture which are very important for initiation and organization of deep convection over a mountain terrain (Bennett et al, ; Demko & Geerts, ; Wang et al, ). It is worth noting that the results from another recent study also demonstrated that the WRF runs initiated with the ERA5 analysis have higher skills in simulation of low‐level jets (mountain valley wind systems) and potential temperatures in Armenia relative to those forced by the GFS fields (Gevorgyan, ).…”
Section: Disscussions and Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter leads to more accurate modeling of low‐level orographically induced flows, convergence centers, and moisture which are very important for initiation and organization of deep convection over a mountain terrain (Bennett et al, ; Demko & Geerts, ; Wang et al, ). It is worth noting that the results from another recent study also demonstrated that the WRF runs initiated with the ERA5 analysis have higher skills in simulation of low‐level jets (mountain valley wind systems) and potential temperatures in Armenia relative to those forced by the GFS fields (Gevorgyan, ).…”
Section: Disscussions and Conclusionmentioning
confidence: 99%
“…Initiation of those convective cells may be induced by low‐level convergence centers due to interaction between cold pool outflows and well‐known valley wind systems with northerly and northeasterly directions blowing to the west and east from Talin station. The valley wind systems in Armenia are induced by regional‐scale heat‐driven plain plateau circulation (Gevorgyan & Melkonyan, ), and those are further enhanced due to funneling effect of river valleys leading to formation of low‐level jets (Gevorgyan, , ). As successfully simulated by the WRF model the valley winds become stronger in the afternoon and evening hours with near‐surface wind speeds reaching up to 10 m/s (Figures h, c, d, g, and h).…”
Section: Synoptic Analysis Of the Extreme Rainfall Eventmentioning
confidence: 99%
“…ERA5 has been validated and shown to give good agreement with radiosonde profiles (Bindu et al, 2018). In additional tests, ERA5 showed improved simulation of near-surface winds at a site near Yerevan, Armenia, with significantly reduced root-mean-square error (RMSE) relative to those forced by the Global Forecast System fields when using ERA5 initial and boundary conditions (Gevorgyan, 2018). Motivated by these good results, we used ERA5 as initial and boundary conditions to simulate fog, because in our tests, fog was sensitive to the near surface southern wind, which brings warm moist air masses over cold water.…”
Section: Model Configurationmentioning
confidence: 99%
“…The entire structure of the simulated atmospheric boundary layer could also depend on the details of PBL schemes and their parameterization of turbulent fluxes of momentum, thereby also potentially affecting the simulation of LLJs. Widely used schemes like the Yonsei University (YSU) and the Mellor‐Yamada‐Janic (MYJ) might produce appropriate representations of low‐level winds and LLJs, with other schemes having similar or even better performance in different situations (Dimitrova et al., 2016; Gevorgyan, 2018; Gómez‐Navarro et al., 2015; Hu et al., 2010; Santos & Nascimento, 2016; Tyagi et al., 2018). For example, Smith et al.…”
Section: Introductionmentioning
confidence: 99%